2022
DOI: 10.1051/e3sconf/202233600006
|View full text |Cite
|
Sign up to set email alerts
|

DFT study on electronic and optical properties of graphene under an external electric field

Abstract: The paper investigates the electronic and optical properties of graphene, under the external electric field (Eext) according to perpendicular direction, using density functional theory (DFT). Applying the Eext to the graphene sheet modifies its electronic and optical properties, including the band gap energy, total density of states (TDOS), absorption coefficient, dielectric function, and refractive index. Graphene’s band gap is opened by the application of Eext to its structure. As a result of the effect of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…These peaks are caused by two fundamental transitions between graphene's electronic states, while the remaining peaks represent the transition of carbon-carbon from the Fermi level-closed state in the region for carbon interaction. The largest peak represents the shift from an occupied to an unoccupied state [52], [53]. In this study, it was found that the 𝜀 ∥ has stronger light penetration compared to 𝜀 ⊥ polarisation with its very high absorption coefficient in the ultraviolet and visible ranges, as reported in several studies [49], [54], [55].…”
Section: Absorption Coefficientsupporting
confidence: 71%
“…These peaks are caused by two fundamental transitions between graphene's electronic states, while the remaining peaks represent the transition of carbon-carbon from the Fermi level-closed state in the region for carbon interaction. The largest peak represents the shift from an occupied to an unoccupied state [52], [53]. In this study, it was found that the 𝜀 ∥ has stronger light penetration compared to 𝜀 ⊥ polarisation with its very high absorption coefficient in the ultraviolet and visible ranges, as reported in several studies [49], [54], [55].…”
Section: Absorption Coefficientsupporting
confidence: 71%
“…Electronic and optical properties of CH 3 NH 3 PbI 3 perovskite are determined by the DFT calculations. These properties are calculated by using the Cambridge Sequential Total Energy Package (CASTEP) [8,9]. The valence electrons in the CH 3 NH 3 PbI 3 structure were represented using ultrasoft pseudopotentials to ensure high precision by the Perdew-Burke-Ernzerhof (PBE) functional within the generalized gradient approximation (GGA) [10][11][12].…”
Section: Methodsmentioning
confidence: 99%
“…The capacity of a substance to allow light to pass through it is quantified by its refractive index, a dimensionless figure that signifies the velocity of light within the material. The subsequent equation can be employed to compute the actual component of the complex refractive index, denoted as [18,19]:…”
Section: Refractive Indexmentioning
confidence: 99%